2004
DOI: 10.1097/01.jnr.0000387483.32944.5c
|View full text |Cite
|
Sign up to set email alerts
|

Study of Basic Computer Competence Among Public Health Nurses in Taiwan

Abstract: Rapid advances in information technology and media have made distance learning on the Internet possible. This new model of learning allows greater efficiency and flexibility in knowledge acquisition. Since basic computer competence is a prerequisite for this new learning model, this study was conducted to examine the basic computer competence of public health nurses in Taiwan and explore factors influencing computer competence. A national cross-sectional randomized study was conducted with 329 public health nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 1 publication
0
13
0
Order By: Relevance
“…These may be significant factors, because earlier studies have shown that women and older persons may have negative attitudes to IT use and poor IT skills (see, e.g. Liu et al . 2000, Yang et al .…”
Section: Discussionmentioning
confidence: 99%
“…These may be significant factors, because earlier studies have shown that women and older persons may have negative attitudes to IT use and poor IT skills (see, e.g. Liu et al . 2000, Yang et al .…”
Section: Discussionmentioning
confidence: 99%
“…However, due to nurses' job rotation and the fixed time and locations of such training courses, they often appear to have low attendance rates and learning outcomes, which result in low learning motivation. The utilization of network education, which provides the most flexible learning method for clinical nurses, will increase nurses' motivation to attend continuing education (Thede, 2001;Yang, Yu, Lin, & Hsu, 2004). The purpose of this study was to investigate the relationship between nursing informatics competency, network education satisfaction and to explore related factors.…”
Section: Introductionmentioning
confidence: 99%
“…Studies published have measured how the level of a student's computer literacy will affect the student's perception of online course work or their satisfaction with virtual learning. 15,16 One study examined the basic computer competence of public health nurses in Taiwan. Findings suggested that public health nurses in Taiwan did not have basic computer competence to succeed in any Web-based online learning modules.…”
Section: Computer Literacymentioning
confidence: 99%
“…Findings suggested that public health nurses in Taiwan did not have basic computer competence to succeed in any Web-based online learning modules. 15 Clear definition of basic computer competence as a requirement for public health nurses was recommended, as well as a systematic assessment program be established. 15 This would aid in planning, designing, and implementing Webbased online learning as a component of continuing education support.…”
Section: Computer Literacymentioning
confidence: 99%
See 1 more Smart Citation